The Myth Awakens: Canon, Conservatism, and Fan Reception of Star Wars - Derry, Ken (Wipf and Stock Publishers, 2018)
Intro -- Title Page -- Acknowledgments -- Contributors -- Preface -- Introduction -- Chapter 1: The More Things Change -- Chapter 2: The Brightest Shadow -- Chapter 3: Leia "the Hutt Slayer" and Rey "the next generation badass boss bitch" -- Chapter 4: I've Heard This Somewhere Before -- Chapter 5: The Racism Awakens -- Chapter 6: Do, or Do Not: There is no Try -- Chapter 7: Ritual, Repetition, and the Responsibility of Relaying the Myth -- Chapter 8: Memory, History, and Forgetting in Star Wars Fandom -- Chapter 9: The Ion Canon Will Fire Several Shots to Make Sure Any Enemy Ships Will be Out of Your Flight Path -- Bibliography.